Digital marketing communication in restaurants of Bangladesh : an in depth study on RainCloud Digital - Ratul, Kazi Ashiqur Rahman (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.